Analysis of The Effect of Profitability, Liquidity, Firm’s Size, and Dividend Policy on Firm’s Value: Empirical Evidence in Non-Cyclicals Consumer Sector Companies - Jul Feryanto; Christina Heti Tri Rahmawati (The Es Accounting And Finance, 2023)
Important factors in assessing whether a company is good or bad can use firm’s size and financial performance. The aim of this research is to analyze profitability (ROA), liquidity (CR), firm’s size (LN), and dividend policy (DPR) on the firm’s value of the consumer non-cyclicals sector which is listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The research population is the consumer non-cyclicals sector companies which are listed on the IDX as many as 57 companies. The research sample is a portion of the consumer non-cyclicals sector companies listed on the IDX that meet the sampling criteria of 20 companies. The sampling technique uses purposive sampling, including non-cyclical consumer sector companies that issue annual reports and financial statements, have positive profits, and have complete data such as total current assets, total current liabilities, total assets, number of outstanding shares, cash dividends, and share prices for the 2017-2020 period. The data analysis technique for this study used multiple linear regression analysis with SPSS 25 software. The results showed that profitability (ROA), liquidity (CR), and firm’s size (LN) had a positive effect on firm’s value, while dividend policy (DPR) had a negative effect on firm’s value in the consumer non-cyclicals sector listed on the IDX in 2017-2020. The implication of the results of this study is that investors should conduct financial analysis before purchasing shares, such as looking at the ratios of profitability, liquidity, and firm’s size; the larger the firm’s value, the better the firm’s value.